Light and life - Abdul Razak, Mariatulqabtiah (Universiti Putra Malaysia Press, 2017)
Since the 10th century B.C., light has been appreciated as a source of energy. Psychologically, a powerful ray of light can induce calmness and excitement in humans. We have been told in the holy books of Islam, Judaism, and Christianity, how the Queen of Sheba (Balqis) had lived with hundreds of windows that allowed beams of sunlight in every morning before she prostrated in front of them. It is probably through this ancient practice that the physician Niels Finsen was inspired to use light to treat diseases and developed the first artificial light source for this purpose back in the 1900s.